Tinjauan Hukum Islam dalam Bisnis Google Adsense di Youtube - Chusein, Muhammad Ali; HW, Maulida Agustina (Journal of Sharia Economic Law, 2023)
A business is an organization that sells goods or services to consumers or other businesses for a profit. Businesses are formed to earn profits and increase the wealth of their owners. Sharia business is limited by how to obtain and manipulate assets so that they are always lawful and reject things that are unlawful. One of the free businesses on the internet is an affiliate program on google adsense. So google adsense provides advertising ads that we don't want even though most of the ad content is about the site. The formulation of this problem is (1) how is the mechanism of cooperation in business on google adsense and random ads on youtube? (2) how is musharakah analysis on business on google adsense and random ads on youtube? The type of research that will be used by the author is field research. While this research approach is qualitative, namely the method presented directly, the relationship between researchers and informants. The data collection technique used by the author is observation and documentation. The data analysis technique used in this study uses qualitative methods to understand the phenomena experienced by the research subjects holistically and by means of description. Based on the research that has been done, the results of business collaborations show that, first, the advertising business on content creator pages in Islam is included in the syirkah category, this is able to provide prospective benefits between the two parties. Second, the practice of cooperation between content creators to provide ad space displayed by Google AdSense is an act that is not in accordance with sharia principles. Because there is still an element of gharar in the specifications for the selection of ads that will be installed or displayed in video content.